Investigation of the Deformation State of a Composite Cable Space Frame Structures with a Photogrammetric Method - Storozhenko, Leonid; Yermolenko, Dmytro; Gasii, Grygorii (International Journal of Engineering and Technology, 2018)
The article presents experimental study results of the deformation state of composite cable space frame structures, including composite steel-concrete structures. Composite cable space frame structures are three-dimensional roof framing of long-span buildings. The designed constructions are a new type of roof framing structures and consist of typical composite steel-concrete modules connected with steel cable elements. The operation of composite cable space frame structures under load is characterised by geometric nonlinearity. The aim of the research is to study the deformation state and changing the geometric shape of experimental structures under the influence of external load. The technique of studying the deformation state of the composite cable space frame structures is based on the principles of digital photogrammetry. At the limit state the composite cable space frame structures change their regular shape. In this case, the central vertical points get the greatest vertical displacements, and the displacement value decreases closer to the supports. It is defined that the investigated construction has demonstrated combined action of all its components during the test, which indicates its effectiveness. The application of the photogrammetry method made possible to determine the moment of reaching the limit state of the composite cable space frame structures concretely.Â Â